Effectiveness of Jacobson’s Relaxation Technique and Yoga in Insomnia Among Shift Working Nurses - Amrin, Babu; Jagatheesan, Alagesan; Vinodhkumar, Ramalingam; Prathap, Suganthirababu; Vignesh, Srinivasan; Kumaresan, Abathsagayam (INTI International University, 2023)
Background: Nurses are one of the main professions in the hospital to recover patients from their abnormal health conditions. The activity of nurses is intimately connected to shift work. Daily shift work results in increased workload and mental stress, which leads to sleep disorder and delayed adaptation for young nurses to shift work, this may cause the nurse’s difficulty falling asleep or insomnia. There is compelling evidence that shift work has a negative impact on sleep, alertness, and exhaustion, which may contribute to mental health issues and sleep issues. Aim: This study aims to find the effectiveness of Jacobson’s relaxation technique and yoga in insomnia among shift nurses. Methodology: In phase 1: The survey was conducted among 100 nurses through Google forms using ISI questionnaires. They were chosen with the help of the convenience sampling technique. Among 100 responded participants, 54% were diagnosed to have insomnia based on the total score range. 20% of selected nurses disagreed to participate in the experimental study (phase 2). Ultimately, 30 nurses were chosen to take part in the experimental trial based on the inclusion and exclusion criteria of phase 2. The participants in the study who had sleeplessness received two therapies. 30 selected nurses were randomly allocated into two groups, 15 in each group. One group was given yoga (Group Y) and another group was given Jacobson’s relaxation technique (Group J). It was given for a time period of 4 days per week for a duration of one month. Results: A statistically significant difference between Group Y (Yoga) and Group J (Jacobson's relaxation technique) was found by statistical analysis of the statistical data. In comparison to Group J, Group Y had lower PSQI values. As a result, group Y and group J differ statistically significantly from one another. Conclusion: It has been concluded that both yoga and Jacobson’s relaxation technique were more effective in improving sleep in nurses with insomnia, among them yoga is more effective than Jacobson’s relaxation technique.